CD8+ T cell-associated genes MS4A1 and TNFRSF17 are prognostic markers and inhibit the progression of colon cancer - Song, Ye; Zhang, Zhipeng; Zhang, Bo; Zhang, Weihui (Frontiers in Oncology, 2022)
Background: Colon cancer (CC) serves as the top three diseases with the greatest morbidity and mortality rates in global cancer statistics. Its increasing incidence imposes a major global health burden. Currently, immune checkpoint inhibitors, for instance, anti-PD-1 and anti-PD-L1, have been verified for the treatment of malignancies, but most patients with CC lack sensitivity to immunotherapy. As a result, the detection of biomarkers to predict immunotherapy sensitivity is crucial for identifying appropriate patients with CC for immunotherapy. Methods: Differential genes linked to the high infiltration of CD8+ T cells were identified in CC and para-cancerous samples using bioinformatics analysis. Prognostic analysis of core genes using Kaplan–Meier survival analysis ascertained that MS4A1 and TNFRSF17 were linked to overall survival in CC. Therefore, experimental verification was performed, and the protein expression level of the target gene was determined with the utilization of immunohistochemical staining in CC tissue and adjacent tumor-free tissue. The proliferation ability, migration ability, and invasion ability of CC cells after the high expression of the target gene were elucidated using in vitro experiments. Results: Bioinformatics differential expression analysis, Weighted Gene Co-expression Analysis, and survival analysis affirmed that individuals with CC having high MS4A1 and TNFRSF17 expressions had longer overall survival. Moreover, the expression of these two genes in CC was discovered to be attenuated in comparison to normal colon tissue, and the expression levels were remarkably linked to the infiltration of various immune cells, including CD8+ T cells in the CC tumor microenvironment (TME). Patients with CC were more sensitive to immunotherapy when MS4A1 and TNFRSF17 expressions were high. Quantitative reverse transcription-polymerase chain reaction, Western blot analysis, as well as Immunohistochemistry experiments showed the differential expression of MS4A1 and TNFRSF17 genes. Furthermore, Cell Counting Kit-8, scratch, and Transwell assays ascertained that the proliferation, migration, and invasion abilities of CC cells were weakened on MS4A1 and TNFRSF17 overexpression. Conclusion: The core genes MS4A1 and TNFRSF17 can be utilized as markers to anticipate the sensitivity of individuals with CC to immunotherapy. Moreover, they have potential applications in gene therapy to inhibit CC progression.